Methodological Basis for Developing the Innovative Model of Regional Educational Environment - K. Y. Komarov (Образование и наука)
The paper reveals the complex research results concerning the essence, content, structural elements and models of modern regional educational environment. The theoretical methodological concepts of developing the innovative model of educational process are given with the reference to the regional educational environment of continuing vocational training. The main emphasis is on methodological bases of the above model of interrelated regional educational establishments within the framework of modernization of vocational training system, including the ideas, concepts, principles and methodological approaches. In particular, the author justifies the necessity for developing and implementing the multilevel methodology effectively applied to developing the theoretical basis of vocational teacher training. The proposed pedagogic technologies, which allow the Russian regional educational system to identify and develop modernization strategies and tactics, are considered to be the condition for the model realization according to the above multilevel methodology.